Mathematical model development of evacuated glass-thermal absorber tube collector (EGATC) for air heating application - Zairul Azrul Zakaria (Tanjong Malim, 2023)
Mathematical model development of evacuated glass-thermal absorber tube collector (EGATC) for air heating application by Zairul Azrul Zakaria